A Single Intramedullary K-Wire Is Sufficient for the Management of Nonthumb Metacarpal Shaft Fractures - Mohamed I. Abulsoud; Mohammed Elmarghany; Tharwat Abdelghany; Mohamed Abdelaal; Mohamed F. Elhalawany; Ahmed R. Zakaria (Advances in Orthopedics)
Objective. This study aims to evaluate the outcome after the internal fixation of diaphyseal metacarpal fractures by a single intramedullary K-wire. Methods. In this prospective case series study, conducted from July 2017 to June 2019 in 23 adult patients with a single, unstable, diaphyseal metacarpal fracture, outcomes after internal surgical fixation using a single antegrade intramedullary K-wire were evaluated. The outcomes were evaluated by union rate, time to union, handgrip measurements at 6 and 12 months, and the modified Disabilities of the Arm, Shoulder, and Hand (DASH) score at 12 months. Results. The study population consisted of 17 males and 6 females, with a mean patient age of 28.4 ± 8.5 years (range, 16–45 years). The median time to final follow-up was 14 ± 1.8 months (range: 12–24 months). The mean duration of the union was 7.3 ± 1.6 weeks (range: 5–11 weeks), with a union rate of 95.7% (22 cases). The mean handgrip strength was 68% ± 12.8% of the strength of the uninjured hand after 6 months and 92.7% ± 6.9% after 12 months. The mean modified DASH score was 2.6 ± 0.26 after 12 months (range: 0–5.8). There were no cases of malrotation or infection. In conclusion, using a single 1.8–2.0 mm K-wire gives excellent functional outcomes and union rate without significant complications when used to treat an unstable metacarpal shaft fracture.